2015
DOI: 10.1371/journal.pgen.1005146
|View full text |Cite
|
Sign up to set email alerts
|

The Orphan Gene dauerless Regulates Dauer Development and Intraspecific Competition in Nematodes by Copy Number Variation

Abstract: Many nematodes form dauer larvae when exposed to unfavorable conditions, representing an example of phenotypic plasticity and a major survival and dispersal strategy. In Caenorhabditis elegans, the regulation of dauer induction is a model for pheromone, insulin, and steroid-hormone signaling. Recent studies in Pristionchus pacificus revealed substantial natural variation in various aspects of dauer development, i.e. pheromone production and sensing and dauer longevity and fitness. One intriguing example is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 37 publications
3
49
0
Order By: Relevance
“…While the insufficient number of recombination events among the 94 RILs did not permit the identification of individual candidate genes, it allows the conclusion that P. pacificus social behaviours are regulated by complex quantitative traits. Furthermore, these data indicate that a substantially larger number of RILs will be necessary to clone individual QTLs, an endeavour that was very successful for other variable traits in P. pacificus strains [30,31]. In C. elegans, a sequence polymorphism in npr-1 underlies the behavioural difference between social and solitary strains [14].…”
Section: (B) Natural Variation In Clumping and Bordering Inmentioning
confidence: 94%
“…While the insufficient number of recombination events among the 94 RILs did not permit the identification of individual candidate genes, it allows the conclusion that P. pacificus social behaviours are regulated by complex quantitative traits. Furthermore, these data indicate that a substantially larger number of RILs will be necessary to clone individual QTLs, an endeavour that was very successful for other variable traits in P. pacificus strains [30,31]. In C. elegans, a sequence polymorphism in npr-1 underlies the behavioural difference between social and solitary strains [14].…”
Section: (B) Natural Variation In Clumping and Bordering Inmentioning
confidence: 94%
“…Although extensive comparative genomic studies did show some evidence of horizontal gene transfer (Dieterich et al 2008;Rödelsperger and Sommer 2011;Meyer et al 2016), this process could only explain the origin of a handful of orphan gene families. In addition to the high abundance of orphan genes within the genome of P. pacificus, we recently showed that most orphan genes are real (Prabh and Rödelsperger 2016) and they can regulate ecologically relevant traits (Mayer et al 2015).…”
mentioning
confidence: 99%
“…with evidence for intraspecific competition, this suggests a process of incipient 106" speciation in P. pacificus [25,26].…”
Section: "mentioning
confidence: 81%
“…-J a p a n R S 5 1 9 7 J a p a n R S 5 1 9 5 J a p a n R S 5 2 1 0 J a p a n R S 5 2 0 8 J a p a n R S 5 2 2 1 J a p a n Table 1 for full location name and its altitude). 26 28 30…”
Section: "mentioning
confidence: 99%